Eksistensi Pondok Pesantren DDI Mangkoso sebagai Lembaga Pendidikan Islam Tradisional: Studi pada Masa Pandemi Covid-19 - Burga, Muhammad Alqadri; Muljono Damopolii; Marjuni (TADRIS: Jurnal Pendidikan Islam, 2021)
The Covid-19 pandemic has forced the transformation of educational civilization, including pesantren education with its traditional characteristics. This study aims to analyze the existence of the DDI Mangkoso Islamic Boarding School as a representation of traditional Islamic educational institutions during the Covid-19 pandemic. The research method used is qualitative with a phenomenological approach. The primary data sources consisted of kiai, ustaz, students, and the community around the DDI Mangkoso Islamic Boarding School. Secondary data sources consist of books, journals, and other relevant scientific works. Data were collected using interview, observation, and documentation methods, then analyzed through three stages, namely data reduction, presentation, and drawing conclusions. The research results show that the DDI Mangkoso Islamic Boarding School still exists as a traditional Islamic education institution by maintaining five roles, namely (1) transmission of classical Islamic sciences, (2) institute of da’wah, (3) preserver of Islamic tradition, (4) center for reproduction of ulama, and (5) place of community service and development.